Numerical simulation on evolution process of molten pool and solidification characteristics of melt track in selective laser melting of ceramic powder. Issue 13 (1st July 2022) - Li, Shengchen; Liu, Defu; Mi, Hangbiao; Deng, Zixin; Liu, Jian; Chen, Tao
Abstract: A three-dimensional high-fidelity physical model for selective laser melting (SLM) of ceramic powder was created based on computational fluid dynamics (CFD) to examine the physical mechanism of molten pool and solidified tracks at mesoscopic scale. The discrete element method (DEM) was used to generate a randomly packed powder bed, and the volume-of-fluid method (VOF) was applied to dynamically monitor the free surface of the molten pool. The formation mechanism and evolution characteristics of the molten pool were found and analyzed, and the effects of laser power on the typical characteristics of solidified ceramic tracks of SLM were investigated. The molten pool was eventually solidified into a concave geometric shape track by surface tension. The laser power played a significant impact on the shaping quality of solidified ceramic track. When the laser power was too low, the melt track suffers from severe porosity and distortion defects, which can be effectively solved with increasing laser power. The simulation results were validated via single track selective laser melting of TiC ceramic powder.